Analysis of high-voltage cascede generator pulsations of a direct current - Бржезицький, Володимир Олександрович; Десятов, Олег Михайлович; Сулейманов, Віктор Миколайович; Хомініч, Віктор Іванович (Technology audit and production reserves, 2015)
In the article the issue of modes calculation for the high-voltage cascade generator with nonlinear loading by means of an analytical method is resolved. For a cascade high-voltage source of a direct current the analytical solution for its pressure and a nonlinear pulsation is found. Research of pulsations amplitude versus oscillator circuit parameters is conducted. The offered analytical method of research for high-voltage installations of a direct current allows perfroming analytical, high precise parameters calculations of cascade voltage generators that is used for the first time. The conducted researches showed that the voltage ripple factor significantly depends on the installation mode of a high direct current voltage and its loading. The obtained results show that the offered analytical method allows perfroming the precise calculations of voltage modes for high-voltage cascade generators with nonlinear loading defining its qualitative characteristics as power supplies of high-voltage technological installations. Carrying out further investigations parameters of a high voltage installations of a direct current with nonlinear loading is relevant and will allow defining its characteristics that influence on quality of the technological processes constructed with use of such units.